2006
DOI: 10.1542/peds.2005-0906
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient-Centered Decision Support on Quality of Asthma Care in the Emergency Department

Abstract: OBJECTIVE. Communication barriers between parents of children with asthma and clinical emergency department (ED) providers and subsequent underrecognition of chronicity and severity impede improvements in disease management for patients with asthma in the ED setting. The asthma kiosk, a novel patient-driven decision-support tool, provides ED clinicians with tailored recommendations for guideline-based treatment. We evaluated the impact of the asthma kiosk on measures of quality during ED care, specifically, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…This finding aligns with previous studies focused on childhood physical illness which showed SDM is associated with greater parental satisfaction with care. (Wilson et al 2010; Porter et al 2006) Examination of interventions to improve SDM as a strategy to increase parent-report of receipt of needed child mental health care is a viable direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with previous studies focused on childhood physical illness which showed SDM is associated with greater parental satisfaction with care. (Wilson et al 2010; Porter et al 2006) Examination of interventions to improve SDM as a strategy to increase parent-report of receipt of needed child mental health care is a viable direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Although the realities of some contexts can make this ideal impracticable, eight examples of researchers using phased approaches (featuring multiple related studies) to development and evaluation of their interventions were found here [8,10,18,21,25,30,65,66,77,78,92-94,102-105,108,109]. …”
Section: Discussionmentioning
confidence: 99%
“…This is an approach highly regarded in boosting the effectiveness of health promotion via behavior change recommendations, [26,28,29] improved patient satisfaction, and more accurate recall of medical advice [30]. Because of the psychosocial factors often associated with obesity and asthma, such as low self-esteem, depression, and low quality of life, [31,32] interventions should benefit from incorporating a patient-centered approach to providing care. This study further illustrates the benefits of seeking and incorporating adolescents' motivations in health behavior change.…”
Section: Discussionmentioning
confidence: 99%